DOES SUSTAINABILITY REPORT ASSURANCE MATTER? SYMBOLIC VERSUS SUBSTANTIVE ESG GREENWASHING - Solikhah, Badingatus (Jurnal Akuntansi dan Keuangan Indonesia, 2026)
Background: Greenwashing reduces the credibility of ESG disclosure by creating a gap between reported information and actual performance. Taiwan offers a relevant context because ESG disclosure is partially mandatory, while sustainability assurance is voluntary. This study investigates how sustainability assurance and institutional pressure influence greenwashing and whether governance quality strengthens these relationships. Method: This study uses panel data of non-financial firms listed on the TWSE and OTC markets from 2017 to 2023. Greenwashing is measured using standardized ESG ratings and ESG controversies, and a peer-relative measure based on Bloomberg and TEJ database is added for robustness. Findings: The results show that sustainability assurance and institutional ownership are negatively associated with greenwashing, suggesting that external verification and investor monitoring enhance the credibility of ESG reporting. Governance quality reinforces these effects, indicating that stronger governance structures respond better to external pressure and are less likely to engage in symbolic ESG practices. These results provide practical insight for regulators and investors in markets with partial or voluntary ESG requirements by showing which mechanisms can help reduce misleading ESG claims. Conclusion: Sustainability assurance, investor oversight, and governance quality jointly reduce opportunistic ESG practices. Novelty/Originality of this article: This study introduces a refined greenwashing measure using ESG ratings and controversies and provides rare evidence on how assurance and governance interact to reduce greenwashing in a partially mandatory disclosure context.